STUDI KOMPARASI PERBUATAN PEMBELAAN DIRI OVERMACHT, NOODWEER DAN NOODWEEREXCES DALAM PERSPEKTIF KITAB UNDANG-UNDANG HUKUM PIDANA: STIH - MUHAMMAD ZAINAL (STIH Zainul Hasan Kraksaan Kraksaan, 2022)
Abstract The Criminal Code that we know is Positive Law that applies in Indonesia, especially those relating to criminal acts or actions that harm others as legal subjects, the Criminal Code (KUHP) is included in the Lex Generalis category or Public Law which regulates the rules for people who commit violations, however, the articles in the Criminal Code do not entirely include paragraphs regarding legal sanctions for perpetrators of criminal acts, but there are several articles that fall into the category of acts that are not criminalized, especially in Book I Chapter III of the Indonesian Criminal Code. the Criminal Law Act which regulates Matters that Eliminate Criminal Offenses which are regulated from Article 44 to Article 52a, in particular the provisions of Articles 48 and 49 of the Criminal Code which regulates Acts of Self-Defense due to Forced Power (overmacht) and Self-Defense The Transcendent / Forced Defense or in other words known as N oodweer, as a form of protection for people who experience an act that threatens themselves so that they carry out a defense, the defense of which of course may have fatal consequences for the perpetrators who turn out to be victims, considering that a few weeks ago there was also a case against the decision at the Jakarta District Court which ruled two the defendant was a police officer who killed Laskar FPI for reasons of Noodweer (defense because he had to). Therefore, the author wants to examine in this research by formulating the problem of how to implement article 48 and article 49 of the Criminal Code regarding self-defense because of compulsion and what are the factors that can be used as justification for self-defense that exceeds the limit/noodweer to ensure legal certainty. The method used in the preparation of this scientific paper is a normative juridical approach which refers to the legislation in force in Indonesia in accordance with the rationale of legal practitioners, as well as legal experts in this country, especially in terms of the application of articles 48 and 49 The Criminal Code (KUHP) on Forced Self-Defense (Overmacht) and Forced Defense (Noodweer) The conclusion of scientific studies on self-defense that exceeds the limit of noodweer in this scientific work is the existence of important and necessary limitations and conditions in terms of self-defense that exceeds the limit or noodweercarried out by victims in defending themselves and their property. Keyword: Comparative Study – Overmach, Noodweer, Noodweerexces – KUHP